A PROFILE OF STUDENTS' SKILLS IN WRITING LITERARY RESPONSES: (A Case Study at English Education Department, Indonesia University of Education) - FIFTINOVA (2010)
This study aims to examine students' skills in writing literary responses. It was conducted in a college level literature class, where one teacher and three students presenting a different level of achievement, were involved. The way the lecturer taught how to write a literary response was captured through observation and students' writings were also documented for providing the data. Moreover, interview with both the lecturer and the students were carried out in order to investigate their perceptions on the writing of literary responses. Data from observation were analyzed by categorizing the class activities and talks which promoted the learning, data from documentation were analyzed by using Functional Grammar, while data from interview were analyzed through thematic analysis. Then, all the data coming from all phases of data analysis were correlated to build a logical chain of evidence. The findings show that the teaching and learning activities are to some extent successfully done by the lecturer. She has applied BKOF, modeling stage and skipped joint construction. In BKOF, the lecturer did reading activity, explanation of theory of reading, class discussion, practice on using appropriate adjective and textual evidence, explaination of guiding questions which are very helpful for constructing the topic of the subject matter. Modeling stage, however, was not conducted well since the lecturer did not explain clearly the linguistic features of literary response text. As a result mid and low achiever students are not really successful in employing tenses and connectives. On the other hand, high achiever is successful in choosing appropriate features of literary response text like connectives, reference to specific people and things, negative and positive vocabulary, present tense and quotation. In terms of schematic structure, the students are capable of adopting all the stages of responding to literary text: introduction, expansion and reaffirmation stage. In spite of that, in introduction stage, the students fail to develop context and background information about general themes of the literary works as suggested by Christie in Couture (1986), Feez and Joyce (2004), and Gibbons (2009). These findings reveal that modelling of writing has not been explicitly and optimally used by the teachers for promoting students' skills in writing literary responses. Finally, data from interview indicate that the students often found it difficult in writing literary responses, specifically in finding appropriate vocabularies. It is also evidenced that the students are familiar enough with literary response text including its purpose, its schematic structures, but not its linguistic features. Finally, the findings show that the teaching and learning activities which effectively facilitate the writing of literary responses are guiding questions in BKOF and text modeling. Consequently, these results reveal that the teaching of content and its appropriate language use in this setting are still taugt implicitly which is contrary to the concept of teaching genre recommended by experts (Butt et al, 2000; Derewianka, 2000; Hammond, 2001; Gibbons, 2009). According to these experts, it is better for the lecturer to induce explicit teaching of text type in subject learning like literature so that students' skills in writing literary responses will be more enhanced. Ultimately, this study recommends that teachers in diverse subject learning, i.e. science, history, mathematics, should induce explicit teaching of text types.